Tax-Induced Emigration: Who Flees High Taxes? Evidence from the Netherlands - José Victor C. Giarola; Olivier Marie; Frank Cörvers; Hans Schmeets (Tinbergen Institute, 2023)
We study the impact of a policy change in the Netherlands that reduced preferential tax treatment duration for high-skilled migrants arriving from specific countries in certain years. Utilizing comprehensive tax and population data, we document substantial tax-induced emigration responses, primarily driven by the top 1% of earners. Highly mobile individuals within the top 5% also emigrate sooner, particularly to competing countries offering tax-breaks to attract skilled workers. Crucially, we uncover no change in mobility behavior among lower-earning workers. The increased tax receipts from lower-income individuals who remain offset the loss from fleeing high earners, making the policy fiscally cost-neutral.
Keywords: F22; H31; J61; 330; Taxation; immigration; labor income; Netherlands